Further Evidence on the Spatio-Temporal Model of House Prices in the United States - BALTAGI, Badi H. (Institutional Knowledge at Singapore Management University, 2014)
Holly, Pesaran, and Yamagata (Journal of Econometrics 2010; 158: 160–173) use a panel of 49 states over the period 1975–2003 to show that state-level real housing prices are driven by economic fundamentals, such as real per capita disposable income, as well as by common shocks, such as changes in interest rates, oil prices and technological change. They apply the common correlated effects estimator of Pesaran (Econometrica 2006; 74(4): 967–101), which takes into account spatial interactions that reflect both geographical proximity and unobserved common factors. This paper replicates their results using a panel of 381 metropolitan statistical areas observed over the period 1975–2011. Our replication shows that their results are fairly robust to the more geographically refined cross-section units, and to the updated period of study.